2012
DOI: 10.2139/ssrn.2182559
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Subjective Sleep Quality in Middle and Old Adulthood and its Relation to Physical Health

Abstract: . The course of subjective sleep quality in middle and old adulthood and its relation to physical health. Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 68(5), 721-729, doi:10.1093 Objectives. Older adults more often complain about sleep disturbances compared with younger adults. However, it is not clear whether there is still a decline of sleep quality after age 60 and whether changes in sleep quality in old age are mere reflections of impaired physical health or whether they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…We found that the prevalence of sleep disturbance increased with age and physical co‐morbidity. Older age was more often associated with sleep disturbance compared with young adults, which is in line with previous studies that report that sleep disturbance increases across the adult life span until age 60 years (Ohayon, Carskadon, Guilleminault, & Vitiello, ; Lemola & Richter, ). Participants with co‐morbidity may experience more physical and psychological burdens depending on the condition they suffer from, and therefore, their sleep quality may be disturbed.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the prevalence of sleep disturbance increased with age and physical co‐morbidity. Older age was more often associated with sleep disturbance compared with young adults, which is in line with previous studies that report that sleep disturbance increases across the adult life span until age 60 years (Ohayon, Carskadon, Guilleminault, & Vitiello, ; Lemola & Richter, ). Participants with co‐morbidity may experience more physical and psychological burdens depending on the condition they suffer from, and therefore, their sleep quality may be disturbed.…”
Section: Discussionsupporting
confidence: 91%
“…Among these thirteen studies, insomnia was heterogeneously defined, although most studies considered insomnia to be simply the presence of difficulty initiating sleep (DIS), difficulty maintaining sleep (DMS), or early morning awakening (EMA). One study defined insomnia symptoms by asking if participants had “trouble” sleeping 19 , while two asked if participants had “problems” sleeping 20, 21 , and another asked “how satisfied are you with your sleep?” 22 . One study also examined hypersomnia (sleeping too much) in addition to DIS/DMS complaints 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Measures of physical health status varied considerably, and included self-reported health status 22, 27, 34, 35 , number of medical conditions/composite variables 19, 21, 23, 24 and/or specific chronic diseases 26, 28, 29 . Studies examining number of medical conditions showed a 70-277% increase in risk for incident insomnia symptoms in participants with 2+ physical disorders 23, 24 , or 4.3 times the odds for those below the median in a physical health status scale 21 .…”
Section: Resultsmentioning
confidence: 99%
“…After 4 weeks, these patients were invited to have an esophagogastroduodenoscopy (EGD) examination to detect PUD recurrence and a RUT, together with a histological examination to detect H. pylori reinfection at 6‐month intervals for up to 36 months, regardless of the presence or absence of PUD symptoms. A previous study identified an effect size of 0.21 between sleep quality and physical health of older adults . We, therefore, adopted a similar effect size of 0.20 that required a minimum sample size of 1054 to achieve a statistical power of 0.9 at a probability level of 0.05.…”
Section: Methodsmentioning
confidence: 99%